2020
DOI: 10.1002/acr.24026
|View full text |Cite
|
Sign up to set email alerts
|

Responsiveness of the Patient‐Reported Outcomes Measurement Information System Global Health Short Form in Outpatients With Systemic Lupus Erythematosus

Abstract: Objective To evaluate the longitudinal responsiveness (sensitivity to change) of the Patient‐Reported Outcomes Measurement Information System (PROMIS) Global Health Short Form (PROMIS10) in outpatients with systemic lupus erythematosus (SLE). Methods Outpatients with SLE who were receiving care at an academic medical center completed the PROMIS10 at 2 visits that were a minimum of 1 month apart. Responsiveness of the PROMIS10 global physical and mental health domains to Patient‐Reported improvement or deterior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Moreover, PROMIS GH scores reported by CDI patients in this study are lower or comparable to other medical conditions. [14][15][16][17][18][19] One caveat for the comparison of these results is that most studies examining HR-QoL are done in the outpatient setting, whereas our study was conducted in the inpatient setting with acutely ill patients. This distinction is highlighted by the fact that the Cdiff32 scores reported by hospitalized patients in our study appear to be lower compared to those reported in the original study by Garey et al, 9 in which preliminary validation was conducted in outpatients.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, PROMIS GH scores reported by CDI patients in this study are lower or comparable to other medical conditions. [14][15][16][17][18][19] One caveat for the comparison of these results is that most studies examining HR-QoL are done in the outpatient setting, whereas our study was conducted in the inpatient setting with acutely ill patients. This distinction is highlighted by the fact that the Cdiff32 scores reported by hospitalized patients in our study appear to be lower compared to those reported in the original study by Garey et al, 9 in which preliminary validation was conducted in outpatients.…”
Section: Discussionmentioning
confidence: 99%
“…Responsiveness was further investigated in 186 patients with systemic lupus erythematosus, using anchors based on self‐ and clinician‐reported global assessments of change. Small to moderate decreases in scores were observed in patients reporting worsening (GPH: ES = −0.27, SRM = −0.37; GMH: ES = −0.54, SRM = −0.68), whereas small increases in scores (GPH: ES = 0.29, SRM = 0.41; GMH: ES = 0.29, SRM = 0.36) were observed in patients reporting improvement . Finally, the PROMIS‐GH version 1.1, as measured in a population of 156 patients with rheumatoid arthritis, ( n = 106 at 12‐week follow‐up visit) showed significant associations between GPH change scores and changes in several disease activity measures, including the Clinical Disease Activity Index (CDAI), tender joints, patient global assessment, and assessor global assessment (standardized β coefficients range from −0.21 to −0.30).…”
Section: Promis Global Healthmentioning
confidence: 98%
“…The PROMIS scores indicate the included participants are generally healthy with global mental and physical health within 1 SD above the mean of the US population, suggesting stable disease, without significant limitations in health-related quality of life. Additionally, in a registry study of patients with SLE, Kasturi et al 22 shows that PROMIS Global-10 correlates well with the patient's perspective of health status. Furthermore, to our knowledge, this is the first study using NGT to ask patients with SLE and myositis of both the benefits and harms of GCs.…”
Section: Discussionmentioning
confidence: 99%
“…Scores are reported as percentiles, with higher scores indicating better health-related quality of life. The PROMIS questionnaire does not correlate well with physician-rated disease activity but is sensitive to change in patient-reported health status and health-related quality of life 22 . Additional information regarding comorbidities, organ involvement, and medication use was obtained by chart review.…”
Section: Methodsmentioning
confidence: 99%